Pengaruh Penambahan Abu Sekam Padi pada Stabilitas Tanah Ditinjau dari Nilai California Bearing Ratio (Studi Kasus: Desa Legoksari) - Algipari, Muhamad Zidan; Agustian, Yanyan (Jurnal Sains dan Teknologi (JSIT), 2026)
Indonesia has a vast territory with diverse soil types, including clay soil, which is commonly found and highly plastic, making it susceptible to volume changes due to moisture fluctuations. Desa Legoksari in Darangdan District, Purwakarta Regency, is one such area dominated by clay soil, leading to construction issues like ground subsidence and structural cracks. To mitigate these challenges, soil stabilization was conducted using rice husk ash (RHA), which contains pozzolanic compounds, primarily silica (SiO₂), known to improve soil strength. This study examines the effect of RHA addition on the California Bearing Ratio (CBR) of clay soil, using mixture variations of 6%, 10%, 14%, and 18% under unsoaked conditions with a one-day curing period. The soil was classified as A-7-6 according to AASHTO and CL (moderate plasticity inorganic clay) according to USCS. The original CBR value of the soil was 7.44%, whereas stabilization resulted in an increasing trend, with values of 10.89% (6%), 13.99% (10%), 20.17% (14%), and 5.66% (18%). Additional tests with 13% and 15% mixtures verified that the 14% composition was the most optimal, yielding CBR values of 15.90% and 16.66%, respectively. These findings confirm that RHA effectively enhances the bearing capacity of clay soil, with an optimal mixture of 14%, which boosts the CBR value by up to 271.10% compared to the original soil condition.